Inductive instructional approach, career aspiration and noble values in history - Mohd Razimi Husin; Hishamuddin Ahmad; Ismail Yusuf Panessai; Norliza Abdul Majid; Agus Lokman Sulam (Institute of Advanced Engineering and Science, 2020)
This paper presents inductive instructional approach, career aspirations and noble values in History. In the 21st century there is still History teachers emphasize the only cognitive aspects of student learning, but still have little to do with everyday life, career aspirations and noble values. This study has developed a review list of learning experiences on specific learning content that takes into account inductive approach, career aspirations and noble values of History subject. Finally, this study examines the effectiveness of the learning that emphasize on the inductive approach, career aspirations and noble values. This study uses a qualitative approach supported by quantitative data involving four stages namely library studies, observations, expert suggestions and quasi-experiments. 30 teachers and 60 students were selected through purposeful sampling. The results show that mean inductive learning experiences, career aspirations and noble values in the subject is higher than the learning with other method. The Inductive-directed delivery approach showed a mean increase of 1.15 in students associate with classroom activities. The results also show that an increase of mean 1.5 and 0.35 in career aspirations and noble values. This study has revealed a checklist of learning experiences, career aspirations and noble values that beneficial to all educators.